2020
DOI: 10.3390/cancers12082075
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Imprinted SLC22A18 and SLC22A18AS Gene Overexpression Caused by Promoter CpG Island Hypomethylation as Diagnostic and Prognostic Biomarkers for Non-Small Cell Lung Cancer Patients

Abstract: Genomic imprinting is a process that involves one gene copy turned-off in a parent-of-origin-dependent manner. The regulation of imprinted genes is broadly dependent on promoter methylation marks, which are frequently associated with both oncogenes and tumor suppressors. The purpose of this study was to assess the DNA methylation patterns of the imprinted solute-carrier family 22 member 18 (SLC22A18) and SLC22A18 antisense (SLC22A18AS) genes in non-small cell lung cancer (NSCLC) patients to study their relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…DNA methylation can not only regulate gene expression but also plays a key role in tumorigenesis [ 27 ]. Previous studies demonstrated that several highly-expressed genes due to hypomethylation were associated with poor prognosis in NSCLC [ 28 , 29 ]. Our results showed that SEC61G expression was associated with SEC61G hypomethylation (R = − 0.290, p < 0.001) and the promoter methylation level of SEC61G in LUAD is lower than that in normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation can not only regulate gene expression but also plays a key role in tumorigenesis [ 27 ]. Previous studies demonstrated that several highly-expressed genes due to hypomethylation were associated with poor prognosis in NSCLC [ 28 , 29 ]. Our results showed that SEC61G expression was associated with SEC61G hypomethylation (R = − 0.290, p < 0.001) and the promoter methylation level of SEC61G in LUAD is lower than that in normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Recent study has demonstrated that the promoter hypomethylation might be served as a prognostic indicators and drug target in lung cancer. 24 In the course of our investigations, the promoter methylation levels of zc3h12d are significantly decreased. And the hypomethylation of zc3h12d may cause a significant increasing in zc3h12d expression.…”
Section: Discussionmentioning
confidence: 65%
“…Despite many mechanisms contributing to elevated gene expression, DNA methylation is one of the most common mechanisms. Sato et al indicated that high gene expression induced by hypomethylation was associated with poor prognosis in NSCLC [ 32 , 33 ]. Through our analysis, we found that hypomethylation is correlated with the high expression level of CANT1.…”
Section: Discussionmentioning
confidence: 99%